Strategies and Innovations in Earthquake-Resistant Housing in Indonesia: Systematic Literature Review - Muhammad Dwi Utomo; Puteri Fitriaty; Irdinal Arief (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
This study aims to identify strategies and innovations in the development of earthquake-resistant housing in Indonesia during the 2015–2025 period through a Systematic Literature Review (SLR). A total of 20 articles were rigorously selected from 233 initial publications in Google Scholar, based on inclusion and exclusion criteria relevant to the local context in Indonesia. The findings reveal three main approaches: (1) modular prefabricated construction systems such as RISHA, RIKO, and RISBA; (2) improvement of conventional construction in accordance with the latest Indonesian National Standards (SNI); and (3) adaptation of vernacular architecture based on local wisdom. The study also examines the performance of materials such as bamboo, timber, steel profiles, light-gauge steel, and composite materials in enhancing earthquake resilience. Architectural studies in Indonesia generally focus on identifying features and concepts of vernacular architecture that are responsive to seismic conditions; however, they have not yet advanced toward the modernization and generalization of these principles for application in earthquake-resistant housing design. Although various technical and social innovations have emerged, implementation in the field remains constrained by weak technical supervision, disparities in construction and material quality, and low disaster literacy among communities. Therefore, this study recommends strengthening technical regulations, enhancing community capacity, and integrating technology with local values as key strategies toward developing earthquake-resistant housing that is contextual, adaptive, and sustainable in Indonesia.